(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to: Determine the cost of banking services. The problem of the research lies in not taking into account a method that measures indirect costs based on ABC activity costs in improving banking services, by building a cost system in the bank, using activity-based costs (ABC), to determine a more accurate and fair cost, more useful in decision-making processes, and because it is more appropriate with the multiplicity of the bank’s activities and the multiplicity and diversity of its services and then improving them, and the high indirect costs in it, and the research also aims to discuss whether costs based on ABC activities represent a system or a method for distributing indirect costs. The basic opportunity that was subjected to the test is that building a cost system in the bank leads to determining the cost of banking services and using activity-based costs (ABC), the cost of banking services is determined more accurately and fairly and then improved. In this research, a cost was built, which is activity-based cost.